2019
DOI: 10.1097/cm9.0000000000000490
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative biomechanical study of positive buttress techniques for femoral neck fractures

Abstract: Background:Refractory femoral neck fractures cannot be anatomically reduced by closed traction reduction which may affect fracture healing. We evaluated the biomechanical effects of positive, negative, and anatomic reduction of various degrees of displacement in Pauwels I femoral neck fractures by a finite element analysis.Methods:Five reduction models of Pauwels type I femoral neck fracture were established using the Mimics 17.0 (Materialize, Leuven, Belgia) and Hypermesh 12.0 (Altair Engineering, Troy, MI, U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Recently, there have also been studies verifying the effectiveness of positive buttress position reduction through biomechanics and animal experiments [ 27 , 28 ]. In 2019, Wang et al [ 28 ] investigated that better biomechanical stability was shown in the positive buttress position reduction group compared to that in the negative buttress position reduction group in a finite element analysis. It was worth mentioning that they further quantified the range of positive buttress and concluded that the range of positive buttress should be controlled within 3 mm as much as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there have also been studies verifying the effectiveness of positive buttress position reduction through biomechanics and animal experiments [ 27 , 28 ]. In 2019, Wang et al [ 28 ] investigated that better biomechanical stability was shown in the positive buttress position reduction group compared to that in the negative buttress position reduction group in a finite element analysis. It was worth mentioning that they further quantified the range of positive buttress and concluded that the range of positive buttress should be controlled within 3 mm as much as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple attempts of closed reduction or open reduction with the aim of anatomical reduction can damage the blood supply of the femoral head and increase the incidence of fracture nonunion or necrosis of the femoral head [ 12 ]. Recently, nonanatomical reductions of FNF, which include positive buttress reduction and negative buttress reduction, have attracted wide attention [ 13 15 ]. The definition of the former is that the distal fracture segments is positioned medially to the lower-medial edge of the proximal segment, while the latter is that the proximal fracture segment is positioned medially to the upper medial edge of the distal segment [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The definition of the former is that the distal fracture segments is positioned medially to the lower-medial edge of the proximal segment, while the latter is that the proximal fracture segment is positioned medially to the upper medial edge of the distal segment [ 16 ]. Since Gotfried et al first proposed the concept of nonanatomical reduction in 2013, numerous studies have compared the effect of nonanatomical reduction and anatomical reduction in FNF [ 10 , 13 15 ]. However, all of these studies focused on internal fixation with CCS.…”
Section: Introductionmentioning
confidence: 99%
“…To study the impact of traction on the cervical vertebra, therefore, a finite element (FE) analysis model of spinal segments is appropriate in which the cervical dysfunctions in the pathologic degenerative condition can be simulated. This computational method provides insight into the detailed biomechanics of the human neck both with and without traction, revealing the impact of tractor on the inner workings of cervical spine [ 16 , 17 ]. Therefore, in this study, the present work investigated the effects of TENB on CSR in the volunteers enrolled as compared with conventional therapy of JOBT.…”
Section: Introductionmentioning
confidence: 99%